Article review: The role of probiotics in maintaining balance intestinal microbiota on diarrhea infection therapy - Nurlaella Solihah; Yani Mulyani; Marita Kaniawati (Science Midwifery, 2025)
Diarrhea infections are a significant global health problem, especially in developing countries and can be caused by bacterial, viral or parasitic infections. Antibiotics are often given times ineffective in long-term use and risk disrupting the balance of intestinal microbiota. So that probiotics are needed that come from living microorganisms that provide health benefits if consumed in sufficient quantities. Review This article aims to review the role of probiotics in maintaining the balance of intestinal microbiota and their effectiveness in diarrheal infection therapy. Through literature analysis, several probiotic strains such as Lactobacillus and Bifidobacterium have shown their ability to inhibit the growth of pathogens, such as Escherichia coli and Clostridium difficile, through nutrient competition, production of antimicrobial substances, and immune modulation. This article concludes that probiotics have great potential as an additional therapy that is safe, effective and has minimal side effects in treating diarrheal infections. However, further studies are needed to determine the optimal dose, duration of use, and effectiveness of probiotics in various populations and types of diarrhea.